Natural history of primary sclerosing cholangitis and prognostic value of cholangiography in a Dutch population. Issue 4 (1st October 2002) - Ponsioen, C Y; Vrouenraets, S M E; Prawirodirdjo, W; Rajaram, R; Rauws, E A J; Mulder, C J J; Reitsma, J B; Heisterkamp, S H; Tytgat, G N J
Abstract : Background: Median survival of patients with primary sclerosing cholangitis (PSC) has been estimated to be 12 years. Cholangiography is the gold standard for diagnosis but is rarely used in estimating prognosis. Aims: To assess the natural history of Dutch PSC patients and to evaluate the prognostic value of a cholangiographic classification system. Patients: A total of 174 patients with established PSC attending a university hospital and three teaching hospitals from 1970 to 1999. Methods: Charts were reviewed for validity and time of diagnosis, concurrent inflammatory bowel disease, interventions, liver transplantation, occurrence of cholangiocarcinoma, and death. Follow up data were obtained from the charts and from the attending clinician or family physician. Median follow up was 76 months (range 1–300). The earliest available cholangiography was scored using a radiological classification system for the severity of sclerosis, developed in our institution. Survival curves were computed by the Kaplan-Meier method. Cholangiographic staging was used to construct a prognostic model, applying Cox proportional hazards analysis. Results: The estimated median survival from time of diagnosis to death from liver disease or liver transplantation was 18 years. Cholangiocarcinoma was found in 18 (10%) patients. Fourteen patients (8%) underwent liver transplantation. Cholangiographic scoring was inversely correlated with survival. A combination of intrahepatic and extrahepatic scoring, together with age at endoscopic retrograde cholangiopancreatography, proved strongly predictive of survival. Conclusions: The observed survival was considerably better than reported in earlier series from Sweden, the UK, and the USA. Classification and staging of cholangiographic abnormalities has prognostic value.